Asymmetries in force matching are related to side of stroke in right-handed individuals. (14th September 2018) - Anderson, Charlie; Rajamani, Kumar; Pardo, Victoria; Adamo, Diane E.
Highlights: Matching hand grasp forces differs between those with a stroke in the right or left hemisphere. Left hemisphere stroke performed better than right hemisphere stroke. Only right hemisphere stroke showed significant asymmetries in contralateral matching. Left hemisphere stroke and controls performed similarly. Abstract: Asymmetries in grasp force matching extend beyond quantifying a single measure of maximum grip strength and advance our application of side-specific treatment interventions. A cross sectional study design investigated grasp-force matching performance in right-handed individuals with a stroke and age-matched healthy controls. A visual representation of the 20% Maximum Voluntary Contraction (MVC) was matched in three conditions in the absence of visual feedback with the same (Ipsilateral Remembered – IR) or opposite hand (Concurrent – CC and Contralateral Remembered – CR). Greater overall relative error (RE) was found in contralateral compared to ipsilateral matching tasks. In the CR condition, post hoc analysis revealed significant differences between control and right hemisphere damage (RHD) group (95% CI [16.41–88.59]; p < 0.01) as well as left hemisphere damage (LHD) group and RHD (95% CI [23.4–95.09]; p < 0.01). Right hand matching relative error was 2.49 times larger in the RHD compared to the LHD group. Within the RHD group, matching errors were greater for the right than left hand in both contralateral conditions (95% CI [34.25–101.07]; p < 0.001). Individuals with RHD showed greater asymmetries in contralateral matching tasks compared to LHD and controls. More specifically, the RHD group had the greatest difficulty matching tasks with their right (non-paretic) than left (paretic) hand. In order to elucidate this asymmetry in the clinic the use of complementary grasp measures may be considered.